Kinetic and stereochemical studies on novel inactivators of C-terminal amidation. - Feng, J (2000)
C-terminal amidation, a required post-translational modification for the bioactivation of many neuropeptides, entails sequential enzymic action by peptidylglycine alpha-mono-oxygenase (PAM, EC 1.14.17.3) and peptidylamidoglycolate lyase (PGL, EC 4.3.2.5). Here we introduce novel compounds in which an olefinic functionality is incorporated into peptide analogues as the most potent turnover-dependent inactivators of PAM. Kinetic parameters for PAM inactivation by 4-oxo-5-acetamido-6-phenyl-hex-2-enoic acid and 4-oxo-5-acetamido-6-(2-thienyl)-hex-2-enoic acid were obtained by using both the conventional dilution assay method and the more complex progress curve method. The results obtained from the progress curve method establish that these compounds exhibit the kinetic characteristics of pure competitive inactivators (i.e. no ESI complex forms during inactivation). On the basis of k(inact)/K(i) values, 4-oxo-5-acetamido-6-(2-thienyl)-hex-2-enoic acid is almost two orders of magnitude more potent than benzoylacrylate, a chemically analogous olefinic inactivator that lacks the peptide moiety. Stereochemical studies established that PAM inactivation by 4-oxo-5-acetamido-6-(2-thienyl)-hex-2-enoic acid is stereospecific with respect to the moiety at the P(2) position, which is consistent with previous results with substrates and reversible inhibitors. In contrast, 2, 4-dioxo-5-acetamido-6-phenylhexanoic acid, which is a competitive inhibitor with respect to ascorbate, exhibits a low degree of stereospecificity in binding to the ascorbate sites of both PAM and dopamine-beta-hydroxylase.